(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2019)
An important problem in an enterprise, related to the labor market, is the selection of appropriate employees, in particular for managerial positions. Enterprises are looking for such employees, whose skills, experience and abilities would lead the company to greater efficiency and further development. The author analyzes the relation between what the labor market offers – education, skills, attitudes of potential employees, and well as the need for specific labor resources from the organization that aims to function effectively. The aim of this article is to indicate the specific features of the selection of employees for positions in combination with the labor market, as well as to emphasize the role of personnel’s selection as a factor affecting the success of the enterprise.